Legal Aspects in Controlling Space Utilization of the Karangsambung Geological Nature Reserve Area, Kebumen Regency: Aspek Hukum dalam Pengendalian Pemanfaatan Ruang Kawasan Cagar Alam Geologi Karangsambung Kabupaten Kebumen - Pujiono, Wasis; Niravita, Aprila (Annual Review of Legal Studies, 2024)
The Karangsambung Geological Nature Reserve Area is an area established by Regional Regulation Number 23 of 2012 concerning the Regional Spatial Plan of Kebumen Regency as a geological protected area that needs to maintain physical and rocky existence and the ecosystem above it for the purposes of education, tourism, and environmental conservation. The problems studied are (1) How is the protection of the Geological Protected Area in the Karangsambung Geological Nature Reserve Area? (2) How is the control of space utilization in the Geological Protected Area in the Karangsambung Geological Nature Reserve Area? This research uses qualitative research methods with an empirical juridical approach. Data sources are primary data and secondary data. Primary data were obtained from the Public Works and Spatial Planning Office of Kebumen Regency, Kebumen Regency Environmental Office, BRIN Karangsambung Geodiversity, and Karangsambung Geopark with interview techniques. Secondary data is obtained from library sources. The results and discussion of this research are (1) Protection of geological protected areas in the Karangsambung Geological Reserve Area through maintaining the integrity of existing geological sites with security from exploitation activities, as well as supporting efforts so that existing rock sites remain sustainable by maintaining drainage, making terracing, reforesting and also carried out disaster mitigation to reduce the impact of disasters. (2) In geological protected areas in the Karangsambung Geological Nature Reserve Area controlling spatial use through several efforts, namely zoning, licensing, incentives and disincentives, and sanctions. The utilization of existing space is going well in terms of education and tourism, but the carrying capacity of the environment for education, tourism, and environmental conservation is not going well because there are still activities that change the geological form in the form of mining in the Karangsambung Geological Nature Reserve Area.